Gereja yang Relevan di Tengah Relativisme Kebenaran dan Generasi Z (Pusat Riset dan Inovasi Nasional, 2026)
The postmodern era has significantly reshaped the way truth is understood, shifting it from an absolute and binding concept to one that is perceived as relative, personal, and context-dependent. This shift has had a profound impact on Generation Z, who have grown up in a digital, pluralistic, and rapidly changing cultural environment. Within this context of increasing truth relativism, the church faces a critical challenge: how to faithfully uphold and teach the absolute truth of the Gospel while remaining relevant to Generation Z, whose worldview is shaped by postmodern patterns of thought. This article examines the concrete challenges encountered by the church amid truth relativism, explores the role and strategies of the church in communicating absolute truth in ways that are meaningful to Generation Z, and proposes practical approaches that can be implemented by local churches today. Employing a literature review methodology, this study engages a range of academic and theological sources related to postmodernism, truth relativism, and faith formation among Generation Z. The findings suggest that the church’s relevance is not achieved through compromising truth, but through presenting the truth of Christ in a contextual, dialogical, and loving manner grounded in authentic relationships. Consequently, the church is called to be a community that not only proclaims truth but also lives it out in tangible ways within the lives of Generation Z.